Study of the associations between polymorphic markers rs1800629 TNFa, rs909253 Lta, rs767455 TNFR1, rs1061624 TNFR2 and the development of type 2 diabetes - Mikhail I. Churnosov; Oksana N. Belousova; Svetlana Sergeyevna Sirotina (Сахарный диабет)
Aim. To study the association between polymorphic genetic markers, tumor necrosis factors and their receptors (rs 1800629 TNFα, rs 909253 Ltα, rs 767455 TNFR1, rs 1061624 TNFR2) and the development of type 2 diabetes (T2D) among the population of the Central Black Earth Region of Russia. Materials and methods. The results obtained from 544 patients, of which 236 were already diagnosed with T2D and 308 were healthy control individuals, were analysed. All the loci were analysed by DNA synthesis using PCR TaqMan probes. The statistical analysis of the frequency distribution of genotypes was performed using contingency tables and the χ2 test, with p ≤ 0.05. Results. A case-control analysis showed that genotype GG rs 909253Ltα was a risk factor for T2D (OR = 2.36, p = 0.01). Also, individuals with genotype AA rs 767455TNFR1 had significantly earlier age of T2D manifestation than that of patients with genetic variants AG and GG (p = 0.01). Conclusion. This study demonstrated the involvement of polymorphic markers of tumor necrosis factors and their receptors in the development of T2D among the residents of the Central Black Earth Region of Russia.